(3x-5)-(x+4)=

Simple and best practice solution for (3x-5)-(x+4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x-5)-(x+4)= equation:


Simplifying
(3x + -5) + -1(x + 4) = 0

Reorder the terms:
(-5 + 3x) + -1(x + 4) = 0

Remove parenthesis around (-5 + 3x)
-5 + 3x + -1(x + 4) = 0

Reorder the terms:
-5 + 3x + -1(4 + x) = 0
-5 + 3x + (4 * -1 + x * -1) = 0
-5 + 3x + (-4 + -1x) = 0

Reorder the terms:
-5 + -4 + 3x + -1x = 0

Combine like terms: -5 + -4 = -9
-9 + 3x + -1x = 0

Combine like terms: 3x + -1x = 2x
-9 + 2x = 0

Solving
-9 + 2x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 9 + 2x = 0 + 9

Combine like terms: -9 + 9 = 0
0 + 2x = 0 + 9
2x = 0 + 9

Combine like terms: 0 + 9 = 9
2x = 9

Divide each side by '2'.
x = 4.5

Simplifying
x = 4.5

See similar equations:

| 15+5x+5x-7+118=180 | | -m^2+13m=0 | | -7g-24=-129 | | 3x-33=7x-5 | | 9x+5-7x=10 | | 87+23+x=180 | | -6-4x+5=-21x+11-4x | | 11x+3-4x=2x-10 | | 11x+3-4x=3x-102 | | 11x+3-4x=3x-12 | | 11x+3-4x=3x-10 | | -3+y+4=5y+17 | | 133+153+x=180 | | 133+153+x=189 | | 5x+2-6x=7 | | 6x-1+7x=2 | | 5y+3-3y=25 | | -1=3-4y | | 136+62+x=180 | | 6=31+5x | | (x-8)+12=16 | | 10-6z=-7z | | -20m-8=60 | | 133+55+x=180 | | 4y-2x-4x-2y= | | -4f+7=35 | | X+27+70=180 | | 5y^2-15y=25 | | 2(ax-3)=8x-b | | 2x+3+25+140=180 | | (ax-3)=8x-b | | 7e+4=5e-18 |

Equations solver categories